Long-Term Non-invasive Ventilation: Do Patients Aged Over 75 Years Differ From Younger Adults? - Cantero, Chloé; Adler, Dan; Pasquina, Patrick; Uldry, Christophe; Egger, Bernard; Prella, Maura; Younossian, Alain Bigin; Soccal-Gasche, Paola; Pépin, Jean-Louis; Janssens, Jean-Paul (Frontiers in Medicine, 2020)
Background: Noninvasive ventilation (NIV) is accepted as standard of care for chronic hypercapnic respiratory failure (CHRF) and is being increasingly implemented in older subjects. However, little is known regarding the use of NIV on a long-term basis in the very old. The outcomes of this study were: 1/to report the proportion of patients ≥ 75 years old (elderly) among a large group of long-term NIV users and its trend since 2000; 2/to compare this population to a younger population (<75 years old) under long-term NIV in terms of diagnoses, comorbidities, anthropometric data, technical aspects, adherence to and efficiency of NIV. Methods: In a cross-sectional analysis of a multicenter cohort study on patients with CHRF under NIV, diagnoses, comorbidities, technical aspects, adherence to and efficiency of NIV were compared between patients ≥ 75 and <75 years old (chi-square or Welch Student tests). Results: Of a total of 489 patients under NIV, 151 patients (31%) were ≥ 75 years of age. Comorbidities such as systemic hypertension (86 vs. 60%, p < 0.001), chronic heart failure (30 vs. 18%, p = 0.005), and pulmonary hypertension (25 vs. 14%, p = 0.005) were more frequent in older subjects. In the older group, there was a trend for a higher prevalence of chronic obstructive pulmonary disease (COPD) (46 vs. 36%, p = 0.151) and a lower prevalence of neuromuscular diseases (NMD) (19 vs. 11%, p = 0.151), although not significant. Adherence to and efficacy of NIV were similar in both groups (daily use of ventilator: 437 vs. 419 min, p = 0.76; PaCO2: 5.8 vs. 5.9 kPa, p = 0.968). Unintentional leaks were slightly higher in the older group (1.8 vs. 0.6 L/min, p = 0.018). Conclusions: In this cross-sectional study, one third of the population under NIV was ≥ 75 years old. Markers of efficacy of NIV, and adherence to treatment were similar when compared to younger subjects, confirming the feasibility of long-term NIV in the very old. Health-related quality of life was not assessed in this study and further research is needed to address this issue.